Redefinition of Englishness in Julian Barnes’s Arthur & George - Naghmeh Varghaıyan (Journal of Literature and Humanities)
Julian Barnes’s Arthur & George (2005) presents a fictional world based on real or historical events and characters. Barnes’s narrative is a re-examination of a historical case, a century later. The narrative depicts how, unlike all his defenders, including the internationally famous detective fiction writer Arthur Canon Doyle, biracial George strives to protect himself by primarily relying on the authority and superiority of British laws. As a solicitor, he defends law as a shared national asset which has the power to produce justice as well as to create a coherent and equal society. However, as a mixed-raced citizen, George is exposed to unsubstantiated accusations. His trial and imprisonment are not based on what he did but on what the communal mind supposes he did. Thus, as this paper argues, race is presented as an integral property of Englishness in Arthur & George. The central problem in this narrative is how the blind pursuit of a racially based understanding of Englishness can drive racial hatred and thus bring about injustice.